Equivalent aqueous phase modulation of domain segregation in myelin monolayers and bilayer vesicles - Oliveira, Rafael G.; Schneck, Emanuel; Funari, Sergio S.; Tanaka, Motomu; Maggio, Bruno (Biophysical journal, 2010)
Purified myelin can be spread as monomolecular films at the air/aqueous interface. These films were visualized by fluorescence and Brewster angle microscopy, showing phase coexistence at low and medium surface pressures (<20-30 mN/m). Beyond this threshold, the film becomes homogeneous or not, depending on the aqueous subphase composition. Pure water as well as sucrose, glycerol, dimethylsulfoxide, and dimethylformamide solutions (20% in water) produced monolayers that become homogeneous at high surface pressures; on the other hand, the presence of salts (NaCl, CaCl2) in Ringer's and physiological solution leads to phase domain microheterogeneity over the whole compression isotherm. These results show that surface heterogeneity is favored by the ionic milieu. The modulation of the phase-mixing behavior in monolayers is paralleled by the behavior of multilamellar vesicles as determined by small-angle and wide-angle x-ray scattering. The correspondence of the behavior of monolayers and multilayers is achieved only at high surface pressures near the equilibrium adsorption surface pressure; at lower surface pressures, the correspondence breaks down. The equilibrium surface tension on all subphases corresponds to that of the air/alkane interface (27 mN/m), independently on the surface tension of the clean subphase.
Gesehen am 14.06.2023